Financial systems in new middle-income African economies: The opportunities and the risks - Alan R. Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper examines the possible implications for the financial systems of low-income African economies and in particular Tanzania of their stated aspiration to achieve middle-income status. In doing so it finds little evidence that the mere increase of gross domestic product per capita will lead necessarily to financial systems that are larger, deeper, or more inclusive. The paper examines both theoretical and econometric evidence to pin down this central conclusion. It also identifies a number of critical structural features that retard progress with financial sector development in some countries and advances a set of plausible hypotheses about the likely sequencing of development in different parts of the financial system - banks, capital markets, pensions, etc.
Keywords: 330; financial development; banks; Tanzania; econometrics; theory